A simple algorithm for computing the smallest enclosing circle - Skyum, Sven (DAIMI Report Series, 1990)
We present a simple iterative algorithm for computing the smallest enclosing circle and the farthest-point Voronoi diagram of a pointset and the ordinary Voronoi diagram of a convex polygon. The algorithm(s) takes O(n log n) time for n points. This is not optimal for any of the problems, but the simplicity of the algorithm(s) makes it a better alternative for medium sized problems than earlier published methods.